Could mobile phone text messages be used for infant feeding education in Ethiopia? A formative qualitative study. (December 2020) - Gebremariam, Kidane Tadesse; Zelenko, Oksana; Hadush, Znabu; Mulugeta, Afework; Gallegos, Danielle
A majority of the world's population now live in areas with a mobile telephone network. This expansion of the network enables people to use more mobile phone functionalities such as short message service, multimedia, and the Internet. Mobile phone–based health (mHealth) interventions have been considered to have benefits in low-income countries. The aim of this study was to explore the feasibility of a short message service for breastfeeding education in Ethiopia. Four focus groups—two with mothers and two with fathers—were conducted with a total of 41 participants. The focus group discussion recordings were transcribed in Tigrigna verbatim, and then translated to English. The data were analyzed using thematic analysis, underpinned by the technology acceptance model. The following four general themes emerged from the focus group discussions: (1) Mobile phones: integrated into everyday life; (2) SMS text messaging: anytime, anywhere, as long as there is a sound; (3) Marketing versus utility: a barrier to SMS; and (4) Scientific messages from credible experts are key to reading SMS-based messages. Parents in Ethiopia showed interest in receiving weekly infant feeding-related short messages. Short message service–based interventions could therefore be an option for improving knowledge and awareness of parents regarding infant feeding.